1995
DOI: 10.1002/ceat.270180113
|View full text |Cite
|
Sign up to set email alerts
|

Vortex depth in unbaffled single and multiple impeller agitated vessels

Abstract: Although vortex formation is usually an undesirable phenomenon in the process industry, satisfactory process conditions and results can also be obtained in unbaffled agitated vessels in the presence of a vortex. This fact and especially the low power requirements in these systems, with their immediate relevance to the energy problem in the process industry, show the true importance of vortex formation in agitated vessels. This article reviews the literature results and the correlations proposed for the predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 6 publications
1
18
0
1
Order By: Relevance
“…However, the free surface profiles predicted by these models qualitatively agree well with that estimated using a correlation given by Markopoulos and Kontogeorgaki (1995). 23 In Fig. 2, we can see that the water surface profiles are unsteady due to the transient nature of the free-surface hydrodynamics in the stirred tank.…”
Section: Profiles Of the Liquid Surfacementioning
confidence: 94%
“…However, the free surface profiles predicted by these models qualitatively agree well with that estimated using a correlation given by Markopoulos and Kontogeorgaki (1995). 23 In Fig. 2, we can see that the water surface profiles are unsteady due to the transient nature of the free-surface hydrodynamics in the stirred tank.…”
Section: Profiles Of the Liquid Surfacementioning
confidence: 94%
“…When the impeller is rotating, a vortex will develop on the surface of the liquid. Many investigators [7][8][9]11 have found that there are two types of motion in the flow of a liquid agitated by a mixer. A zone with a constant angular velocity (vortex zone) is formed in the central part of the vessel, and a zone where the peripheral velocity of the liquid decreases according to the hyperbolic law (irrotational zone) is formed in the remaining part.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…The tangential component of velocity (v t ) is continuous in r but a break appears at r 0 . Assuming that the axial flow is very small and therefore negligible in comparison with the tangential liquid flow and there is no contribution from the continuity equation 8 , the r and z components of the equation of motion can be expressed as 7,14 :…”
Section: Theoretical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study of the formation of vortex in an unbaffled stirred tank is very important to understand the air-entrainment at particular power consumption. So, study of vortex formation caused by an unbaffled condition of the system is closely associated with power consumption in the system as it is widely known that the unbaffled system consumes less power [4,5] than the baffled system. Therefore, study on vortex formation in agitated vessels to save energy in terms of power consumption is required [6].…”
Section: Introductionmentioning
confidence: 99%